Chapter System, Hypothesis, and Experiments: Pierre-Sylvain Régis - DEL PRETE, Antonella (Knowledge and its Histories, 2023)
Pierre-Sylvain Régis's Cartesianism is quite singular in seventeenth-century French philosophy. Though, can we speak of a form of experimental science in Régis's work? After exploring his notions of 'system' and 'hypothesis', I will define his position in relation to Claude Perrault, Jacques Rohault, and the Royal Society. I argue, first, that the contrasts which traverse French science are not so much about the use of experiments but about whether or not observational data can be traced back to hypotheses and to a coherent system. Secondly, that we can detect a significant similarity between Boyle's positions and the views expressed by Perrault and also by Régis. Lastly, that French science, even in its Cartesian version, is much more probabilistic than English experimental philosophy.